One-pot synthesis and characterization of polyynes end-capped by biphenyl groups (α, ω-biphenylpolyynes). (January 2018) - Cataldo, Franco; Ursini, Ornella; Milani, Alberto; Casari, Carlo S.
Abstract: Stable polyyne chains terminated with biphenyl end groups (α, ω-biphenylpolyynes) were synthesized in a single step through a simple procedure by using the Cadiot-Chodkiewicz reaction conditions. The α, ω-biphenylpolyynes were separated through HPLC analysis and identified by means of their electronic absorption spectra. The α, ω-biphenylpolyynes were studied by FT-IR and Raman spectroscopy and the spectral interpretation was supported with DFT calculations. A peculiarly low reactivity of α, ω-biphenylpolyynes with ozone was observed. Graphical abstract: Image